Relaxin and HFpEF: unveiling a new contributor to personalized medicine? - Benedita Almeida Pires Couto Viana (2022)
Aims Although Heart Failure with Preserved Ejection Fraction (HFpEF) is a growing health problem, there are still significant caveats on the understanding of its pathophysiology, diagnosis and treatment. We aimed to evaluate the role of Relaxin-2 (RLX2) circulating levels on the diagnosis of chronic HFpEF and to explore their association with HFpEF-related risk factors/comorbidities. Methods and Results We performed a cross-sectional analysis of a prospective cohort study (NETDiamond), evaluating 85 chronic HFpEF and 16 control patients. Serum RLX2 concentration was measured at enrolment and its values were compared between groups. Associations between patients' characteristics and RLX2 were evaluated using linear regression models adjusted for age, sex and glomerular filtration rate. No significant differences were found in RLX2 levels between controls and HFpEF patients (mean log2-RLX2 4.64±2.28 vs. 4.80±2.30pg/mL respectively, p=0.798). RLX2 levels were higher in females (5.4±2.0 vs.4.3±2.4pg/mL, p=0.014). Also, they were negatively associated with a history of myocardial infarction (β=-1.3, p=0.018), peripheral artery disease (β=-1.4, p=0.027) and statin use (β=-1.7, p=0.002) and positively associated with obstructive sleep apnea (β=1.1, p=0.028). Regarding analytical parameters, RLX2 was positively associated with C-peptide (β=-1.3, p=0.018), phosphate (β=1.3, p=0.003), uric acid (β=0.33, p=0.001) and HDL (β=0.04, p=0.023) and negatively associated with HbA1c (β=-0.48, p=0.012). Conclusion RLX2 did not significantly differ between HFpEF and control patients. However, it might be useful in HFpEF patients' phenotypic characterization, due to its negative correlation with ischemic vascular disease and association with glycemic metabolism. These associations may contribute to a more personalized approach to HFpEF, needing further exploration.